Puncture, drainage and irrigation: Is that enough for treating an abscess? - Gajiwala Kalpesh (Indian Journal of Plastic Surgery)
An abscess is a common occurrence. The gold standard for treatment is incision and drainage. Here a simple technique of a small puncture followed by drainage and irrigation done under local anesthesia is described. Sixty-four patients were treated between 1990 and 2006. Barring two, which were taken off the study, all healed completely without recurrence. The advantages of this procedure are that it is simple, can be done as an office procedure enabling a quick return to work and results in faster, scar free healing. It also allows better pain management.